2008
DOI: 10.1248/bpb.31.1237
|View full text |Cite
|
Sign up to set email alerts
|

Development of Small, Homogeneous pDNA Particles Condensed with Mono-cationic Detergents and Encapsulated in a Multifunctional Envelope-type Nano Device

Abstract: Non-viral DNA vectors are promising gene delivery systems and a variety of non-viral DNA vectors have been developed to date. Recently, we developed a novel non-viral gene delivery system-multifunctional envelope-type nano device (MEND). The MEND system has high transfection activity, similar to that of adenovirus vector, which is a potent viral vector. However, conventional MEND is relatively large and heterogeneous (approximately 300 nm), probably because they contain relatively large-and heterogeneous-pDNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…We considered that Type-E MCDs, which have an L-chain and an aromatic group, may form siRNA/MCD nanoparticles more effectively than Type-C and -D MCDs, due to the greater hydrophobicity of Type-E MCDs. A similar tendency was also observed when pDNA was used [20]. In the case of MCDs containing a dodecyl group L-chain (E-1), aggregation was observed at high N/P ratios, although negatively charged nanoparticles were formed at low N/P ratios.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…We considered that Type-E MCDs, which have an L-chain and an aromatic group, may form siRNA/MCD nanoparticles more effectively than Type-C and -D MCDs, due to the greater hydrophobicity of Type-E MCDs. A similar tendency was also observed when pDNA was used [20]. In the case of MCDs containing a dodecyl group L-chain (E-1), aggregation was observed at high N/P ratios, although negatively charged nanoparticles were formed at low N/P ratios.…”
Section: Resultssupporting
confidence: 66%
“…In this experiment, we prepared the R8-D-MEND containing an siRNA nanoparticle complexed with the E-3 MCD, which showed high transfection activity as a DNA condenser [20]. Gene silencing efficiencies after 12, 24, 48 and 72 h of transfection are shown in Figure 2A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…poly‐ L ‐lysine) interact with pDNA molecules through a highly cooperative process, leading to condensation of multiple molecules of pDNA. This process has been found to be quasi‐irreversible 112, 113 and leads to formation of relatively large particles containing multiple pDNA molecules per particle. Unlike polycations, interaction of pDNA with oligo‐ and mono‐cationic detergents is reversible and condenses pDNA into discrete particles that might contain only one pDNA molecule.…”
Section: Polymer Microparticles Liposomes and Nanoparticles As Vehimentioning
confidence: 99%
“…The solubility and unfolding of DNA in mono‐cationic detergent condensed pDNA formulations requires additional stabilization for effective transfection of cells in vivo . Stabilized monomolecular plasmid DNA nano‐particles (∼60 nm) packaged into a lipid bilayer and loaded with the cell‐penetrating peptide octaarginine generated particles of ∼100 nm diameter with low toxicity and transfection efficiencies similar to Ad vector and the larger poly‐ L ‐lysine membrane particles 112, 113. A recent study showed that poly‐propylene sulfide polymer 20 nm particles could enter lymphatic vessels and targeted 50% of resident lymph node DC and macrophages without the need for specific targeting molecules 108.…”
Section: Polymer Microparticles Liposomes and Nanoparticles As Vehimentioning
confidence: 99%